Biodiesel production using cellulose-supported calcium hydroxide heterogeneous catalyst. phosphate rock as a catalyst precursor - Kiprono, Janet Jematia (Vaal University of Technology, 2022)
Due to rising gasoline prices and growing worldwide worries about climate change and environmental pollution, the need for a clean, environmentally friendly fuel such as biodiesel has recently gained traction. This has demanded greater study into more efficient techniques to boost biodiesel production. The current study focuses on making and improving the efficiency of calcium hydroxide heterogeneous catalyst to be used in biodiesel manufacturing from waste cooking oil. Phosphate rock, a primary mineral mined in South Africa, containing the compound calcium carbonate in higher quantities, was used to prepare calcium nitrate, a useful compound in nature. Calcium nitrate was then reacted with cellulose nanoparticles and sodium hydroxide solution to obtain cellulose-supported calcium hydroxide catalyst through the co-precipitation method. Characterization techniques such as SEM and FTIR were used to confirm calcium hydroxide loading on the cellulose support material. The efficiency of the synthesized catalyst in the transesterification process was studied by varying the alcohol to oil ratio, amount of catalyst, the reaction temperature, reaction time, and the reusability cycles of the catalyst through one factor at a time method and response surface methodology. Artificial neuron network was later used in the prediction of biodiesel yield. High regression coefficient values were obtained, indicating the efficiency of artificial neuron network tool in the prediction of biodiesel. Calcined phosphate rock is also tested for use as a heterogeneous catalyst for biodiesel production. This is based on the fact that when calcium carbonate in the rock is subjected to extremely high temperatures, the carbonates undergo decomposition releasing carbon iv oxide gas thus forming calcium oxide. This oxide also proved to be an active catalyst for transesterification. The efficiency of this catalyst was also tested through one factor at a time and response surface methodology. Both cases obtained a higher biodiesel yield.
M. Tech. (Department of Chemical Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Biodiesel production; Calcium hydroxide heterogeneous catalyst; Waste cooking oil; Biofuels; Phosphate rock; Nanotechnology; Catalyst; Dissertations, Academic -- South Africa.; Biodiesel fuels.; Catalysts.; Vegetable oils.